Necessity as a ground for precluding wrongfulness in international investment law - Vasiljević Mirko; Jovanović Marko (Anali Pravnog Fakulteta u Beogradu)
The issue of necessity as a ground for precluding wrongfulness has received close attention over the last two decades both in case law and in scholarly writings. Arbitrations conducted against Argentina for breaches of bilateral investment treaty obligations committed while fighting against economic crisis revived the old controversies related to the concept of necessity in general public international law, but also brought up some new dilemmas. This paper analyses the use of necessity in international investment law in light of what the authors suggest to be the legal purpose of this concept, points to and discusses the divergences in case law with respect to some of the elements of the defence based on necessity and offers the solutions susceptible to lead to a more harmonious understanding of necessity in international investment law.